2015
DOI: 10.5380/abclima.v16i0.40585
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem Espacial Da Ilha De Calor Urbana Em Presidente Prudente (Sp) – Brasil

Abstract: O diagnóstico das ilhas de calor urbanas tem se mostrado um instrumento importante para a gestão do espaço urbano, na medida em que a espacialização das diferenças das temperaturas intraurbanas e rurais próximas pode oferecer subsídios para que atitudes possam ser tomadas com o objetivo de amenizar a magnitude de tais ilhas de calor. Entretanto, as interpolações dos registros de temperaturas do ar que não levam em consideração as características dos alvos superficiais produzem resultados que dificultam interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
26

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 4 publications
0
17
0
26
Order By: Relevance
“…Nevertheless, a different pattern has been identified throughout small-and medium-sized cities in Brazil, where neighborhoods far from the urban core show higher temperatures [18,23,[54][55][56]. Surface heterogeneities are associated with the formation of one or more heat islands that are not necessarily located in the old core.…”
Section: Urban Morphology Land Cover and Uhi Magnitudementioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, a different pattern has been identified throughout small-and medium-sized cities in Brazil, where neighborhoods far from the urban core show higher temperatures [18,23,[54][55][56]. Surface heterogeneities are associated with the formation of one or more heat islands that are not necessarily located in the old core.…”
Section: Urban Morphology Land Cover and Uhi Magnitudementioning
confidence: 99%
“…Heat islands are defined by easily measurable parameters, and various studies on urban climate have reported UHIs in Brazil [18,23,24,[26][27][28][29]. Typically, air temperatures are measured using either thermometers via mobile surveys or a stationary network of sensors.…”
Section: Measuring Uhis In Small-and Mid-sized Citiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the route was chosen based on topography and soil cover diversity (Figure 1). Heat islands are well-defined at evening hours (Amorim et al, 2015). Thus, measurements were taken at 20h (local time) on the 15th, 20th and 21st of August, 2012 (winter) and on the 26th, 27th and 28th of February, 2013 (summer).…”
Section: Meteorological Data Collectionmentioning
confidence: 99%